Comparison of Different Cycloplegic Refraction Regimens for Children - Irfani, Irawati; Gunawan, Fany; Satari, Karmelita; Sari, Maya; Oktarima, Primawita; Caesarya, Sesy; Karfiati, Feti (Majalah Kedokteran Bandung, 2024)
In the process of a pediatric eye exam, cycloplegic refraction is a crucial step. Since no single cycloplegic drug is ideal, a combination regimen is employed. This study compares the ocular (refractive power and pupil diameter) and systemic (blood pressure and heart rate) effects of administering a combination of 1% cyclopentolate and 2.5% phenylephrine, with or without 1% tropicamide, to children with refractive errors. This study aimed to discover a more feasible regimen for children. This was a single-blind study, a randomized clinical trial conducted from November–December 2020 in children with mild to moderate refractive errors. Group A received 1% cyclopentolate, 2.5% phenylephrine, and 1% tropicamide (SFT), whereas group B received 1% cyclopentolate and 2.5% phenylephrine (SF). The outcomes were measured using an auto refractometer and IOL Master® 700. Before and 60 minutes after medication was administered, blood pressure and heart rate were measured. There were 54 participants (108 eyes) with an average age of 12.85± 2.84 years. Although the SFT group's refractive power and pupil width were greater than those of the SF group, the differences were not statistically significant (p=0.271 and p=0.088). Heart rate (p=0.521) and blood pressure (systolic p=0.201; diastolic p=0.950) did not significantly differ between the two groups. Despite mydriasis manifested more rapidly in the SFT group, there was no discernible difference in the cycloplegic effects between those groups. SF might be a more feasible regimen for cycloplegic refraction in children with refractive errors.